Tools for Thought: Research and Design for Understanding, Protecting, and Augmenting Human Cognition with Generative AI - Tankelevitch, Lev; Glassman, Elena L.; He, Jessica; Kazemitabaar, Majeed; Kittur, Aniket; Lee, Mina; Palani, Srishti; Sarkar, Advait; Ramos, Gonzalo; Rogers, Yvonne; Subramonyam, Hari (ACM CHI Conference on Human Factors in Computing Systems (CHI 2025), 2025)
CHI 2025 Workshop on Tools for Thought: Research and Design for Understanding, Protecting, and Augmenting Human Cognition with Generative AI. The workshop is part of the ACM (Association of Computing Machinery) CHI conference on Human Factors in Computing Systems. The workshop takes place Saturday, April 26, 2025 — 9AM-5:50PM JST — Yokohama, Japan. CHI takes place in Yokohama, Japan, from 26 April to 1 May 2025. Workshop abstract: We invite researchers, designers, practitioners, and provocateurs to explore what it means to understand and shape the impact of Generative AI (GenAI) on human cognition. GenAI radically widens the scope and capability of automation for work, learning, and creativity. While impactful, it also changes workflows and the quality of thinking involved, raising questions about its effects on cognition, including critical thinking and learning. Yet, GenAI also offers opportunities for designing tools for thought that protect and augment cognition. Such systems provoke critical thinking, provide personalized tutoring, or enable novel ways of sensemaking, among other approaches. How does GenAI change workflows and human cognition? What are opportunities and challenges for designing GenAI systems that protect and augment human cognition? Which theories, perspectives, and methods are relevant? This workshop aims to develop a multidisciplinary community interested in exploring these questions to protect against the erosion, and fuel the augmentation, of human cognition using GenAI. Workshop website: https://aka.ms/toolsforthoughtworkshop